Users' Perception Towards UUM Community Portal - Barakat, Bashar Hasan Mohammad (2009)
This study explored the benefits that are perceived by Universiti Utara Malaysia’s(UUM) supporting staff to be achievable through the implementations of UUM Community Portal, and also to examine users’ satisfaction towards the system. 78 respondents from 6 departments and 1 college at UUM participated in this study. The findings show that participants perceived “quick response and access to information” as the major benefit in adopting UUM Community Portal. However, “improve accuracy and enhance competitiveness” were perceived by the participants as having less benefit.Results also show that participants’ age and education level did not influence their perception towards the benefits in adopting the system.In terms of satisfaction level, participants generally felt satisfied with the system, and this includes all the five dimensions, namely the content, format, accuracy, timeliness and ease of use. However, ease of use was one aspect of the system that participants felt most satisfied with, and content generated by the system was the aspect that participants felt least satisfied with. Participants’ age did not influence the feelings of satisfaction but, participants with high education level were found to be less satisfied than participants with low education level (secondary education).In conclusion, the results from this study indicate that currently users of UUM Community Portal, the supporting staff, perceived that there are benefits of adopting the system and they are generally satisfied with the system.